'One Giant House': Civil Society Mobilisation and the Protection of Palestinian Cultural Heritage and Identity in Al-quds Al-Sharif. Issue 1 (May 2018) - Smith O'Neil, Maryvelma
Abstract : Civil society organisations in East Jerusalem play a crucial role in protecting Palestinian cultural heritage in the Old City of Jerusalem by providing grassroots support and enhancing the steadfastness of East Jerusalem's Palestinian residents. In critically engaging with the Palestine National Authority's (PNA's) definition of the role of culture, this article seeks to provide the first comprehensive assessment of this civil society mobilisation. After breaking new ground by demonstrating how Jerusalemite university students perceive Palestinian identity, it concludes by asserting that the forging of an active collaboration between the PNA, Jerusalemite students and minority communities could bolster the frontline defense of vulnerable cultural heritage against further Zionist remodeling of Jerusalem's 'one giant house'. (Ghoshen 2013 )